Effect of granule organisation on the behaviour of starches in the NMMO (N-methyl morpholine N-oxide) solvent system - Koganti, Nagamani; Mitchell, John; Macnaughtan, William; Hill, Sandra E.; Foster, Tim (Elsevier, 2015)
The response of starches of different botanical origin to heating in 78% N-methyl morpholine N-oxide (NMMO) is compared with their behaviour in water. For all starches studied an exothermic transition is obtained in the NMMO system rather than the endothermic transition in water. In NMMO the transition temperatures are lower for A-type starches (wheat, rice and tapioca) than the C-type starches (sago and pea) and also potato which has a B-type polymorph. Observations using a hot stage microscope show two different types of initial behaviour in NMMO; erosion of the granule from the surface or disruption into fragments. In both cases the final outcome is dissolution but for the most resistant C-type starches (pea and sago) some intact granules could be seen following heating at 95 °C in 78% NMMO and subsequent precipitation in ethanol. The results are discussed in terms of what is known from previous structural studies on these six starches and the behaviour of maize starch in NMMO and ionic liquids. The work is relevant to the co-dissolution of starch and cellulose to form novel polysaccharide based materials.